2015
DOI: 10.1002/ddr.21235
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin Induces Antiproliferative Activity Against Human Hepatocellular Carcinoma (HepG2) Cells by Suppressing Specificity Protein 1 (Sp1)

Abstract: Preclinical Research Quercetin, found in red onions and red apple skin can induce apoptosis insome malignant cells. However, the apoptotic effect of quercetin in hepatocellular carcinoma HepG2 cells via regulation of specificity protein 1 (Sp1) has not been studied. Here, we demonstrated that quercetin decreased cell growth and induce apoptosis in HepG2 cells via suppression of Sp1 using 3-(4,5-dimethyl-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium, inner salt (MTS) assay, 4',6-diamidino-2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…In addition to ephrins, other dependence receptor ligands, PI3K, AKT, and serpines, we anticipate that drugs that target p21, probably p53 and MDM2 (because they regulate p21 and serpines), BCL-xL, and related genes will also have senolytic effects. This is especially so as existing drugs that act through these targets cause apoptosis in cancer cells and are in use or in trials for treating cancers, including dasatinib, quercetin, and tiplaxtinin (Gomes-Giacoia et al ., 2013; Truffaux et al ., 2014; Lee et al ., 2015). …”
Section: Discussionmentioning
confidence: 99%
“…In addition to ephrins, other dependence receptor ligands, PI3K, AKT, and serpines, we anticipate that drugs that target p21, probably p53 and MDM2 (because they regulate p21 and serpines), BCL-xL, and related genes will also have senolytic effects. This is especially so as existing drugs that act through these targets cause apoptosis in cancer cells and are in use or in trials for treating cancers, including dasatinib, quercetin, and tiplaxtinin (Gomes-Giacoia et al ., 2013; Truffaux et al ., 2014; Lee et al ., 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Jeon et al reported an increase in p53 levels and a decrease in cyclin A and checkpoint kinase 1 (CHK1) expression in HepG2 cells after quercetin treatment [25], while this drug downregulated p53 and enhanced G0/G1 and G2/M populations in HepG2 and HuH7 HCC lines [51]. Augmented levels of p21 and p27, cell cycle inhibitors, and cyclin D1 reduction were observed in another study with HepG2 cells [33] and it has been also shown that quercetin promoted G0/G1-phase arrest [49,52,53] through upregulating p16, p21 and p53 [53]. Conversely, a cell cycle arrest at G2/M phase has been described as a quercetin effect against HCC cell proliferation in HepG2 [30] and LM3 liver cancer lines [22].…”
Section: Antitumor Properties Of Quercetin As Single Agent Against Hccmentioning
confidence: 94%
“…Quercetin antitumor effects have been described in different cancer types, including HCC [1]. In 25 of the articles included in the present review, quercetin efficacy as single treatment was evaluated employing different HCC study models [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]46,48,49,[51][52][53][54]57]. Antiproliferative effect of this flavonoid alone has been demonstrated in several researches with in vitro models [22][23][24][25][26][27][30][31][32][33]35,38,46,48,49,[51][52][53][54], highlighting the HepG2 cell line as the most used in 21 of the 25 articles [24,25,<...>…”
Section: Antitumor Properties Of Quercetin As Single Agent Against Hccmentioning
confidence: 99%
See 2 more Smart Citations